PEMAHAMAN MASYARAKAT TERHADAP MARKA JALAN “YELLOW BOX JUNCTION”DI KOTA DENPASAR - Cokorda Putra Wirasutama; Tjokorda Istri Praganingrum (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
One way to solve the problem in reducing congestion, especially at intersections, is to apply the yellow box junction rule. The objective of installation of yellow box at the intersection is for vehicles not to pile up at one point. The order is that vehicle should not be in the yellow box as long as the vehicle in front of it has not fully passed the yellow box. This method is used so that the opposite direction vehicle can pass through the intersection without being blocked by the vehiclefrom the opposite direction. This condition will cause the vehicles at the intersection flow smoothly, and do not experience delays due to accumulation of vehicles from opposite directions. This study will evaluate the application of yellow box junction rules at intersections in Denpasar City. The results of the interviews were analyzed by comparing the ratio between the person/s who understood about the yellow box to all the samples interviewed. Result of the data analyzed is that the average person that understood about the yellow boxjunction is 60%.